New genus and new species of Pentatomidae from Borneo (Hemiptera: Heteroptera) - Roca-Cusachs, Marcos; Rider, David. A.; Jung, Sunghoon (Zootaxa, 2021)
A new genus, Graziasternum gen. nov., with two new species, Graziasternum graziae sp. nov. and Graziasternum joceliae sp. nov. are described. According to external thoracic and genital structures, this new genus is considered to be the closest extant relative known to the genus Placosternum Amyot & Serville. Discussion of its possible phylogenetic position based on structure comparison, with the discussion on the importance of the characteristics of the thoracic sterna, the genital structures with other genera or groups of genera that share similar structures is given. Additionally, the two new species are keyed and illustrated.